(untitled) - Lackner, Maximilian (Weinheim, 2013)
More than ninety-percent of global energy production is based on combustion. Providing a concise, easy-to-understand introduction to this important topic, 'Combustion' focuses on practical aspects rather than theory.
Keywords: Combustion,Bốc cháy